2011
DOI: 10.1111/j.1476-5381.2010.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of new analgesics

Abstract: Patient phenotypes in pharmacological pain treatment varies between individuals, which could be partly assigned to their genotypes regarding the targets of classical analgesics (OPRM1, PTGS2) or associated signalling pathways (KCNJ6). Translational and genetic research have identified new targets, for which new analgesics are being developed. This addresses voltage-gated sodium, calcium and potassium channels, for which SCN9A, CACNA1B, KCNQ2 and KCNQ3, respectively, are primary gene candidates because they cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 173 publications
0
27
0
Order By: Relevance
“…These mainly include genes found, in at least three independent studies in transgenic mice, to contribute to the modulation of pain and identified using PubMed searches, with the addition of further genes (Lötsch et al., ) comprising those causally implicated in human hereditary diseases associated with extreme pain phenotypes (summarized in, e.g. Lötsch et al., ), and genes coding for the targets of approved analgesic drugs or of novel analgesics currently in clinical phases of development (Lötsch and Geisslinger, ). This provided a set of n = 535 ‘pain genes’ (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…These mainly include genes found, in at least three independent studies in transgenic mice, to contribute to the modulation of pain and identified using PubMed searches, with the addition of further genes (Lötsch et al., ) comprising those causally implicated in human hereditary diseases associated with extreme pain phenotypes (summarized in, e.g. Lötsch et al., ), and genes coding for the targets of approved analgesic drugs or of novel analgesics currently in clinical phases of development (Lötsch and Geisslinger, ). This provided a set of n = 535 ‘pain genes’ (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…15 Based on this observation, we studied 207 patients with the aim to include between 20 and 40 patients who could have the A118G SNP. All patients were enrolled under Institutional Review Board of the Hospital CLINIC de Barcelona, Barcelona, Spain, approval of the study protocol and they signed an informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Signal transmission from opioid receptors requires involvement of ion channels (K, Na, Ca) and polymorphisms of these channels have also been noted to have an influence on pain sensitivity. Mutations in voltage-gated transient receptor potential channels have been identified and may modulate the effects of analgesics [95]. Efflux transporters like the P-glycoproteins are also associated with polymorphisms and may affect transport into or out of the brain [96].…”
Section: Further Pharmacogenomic Influencesmentioning
confidence: 99%